Pembinaan Dan Pendampingan Pembuatan NIB Oleh Mahasiswa Dalam Rangka Memajukan UMKM Sari Kedelai Sidoarjo - Khoirun Nisa; Lulu Nazma Lailatul Muchlis; Naswa Ika Febrianty; Nafia Ilhama Qurratu’aini (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The improvement of micro, small and medium enterprises (MSMEs) plays a significant role in driving the local economy. One of the crucial steps in developing MSMEs is through coaching and mentoring in the licensing process, including the creation of a Business Identification Number (NIB). This study aims to examine the coaching and mentoring conducted by students in making NIBs to advance soybean juice MSMEs in Sidoarjo. This research was conducted using qualitative methods through observations and interviews with Ms. Diah as the owner of the soybean juice business in Gading Fajar Sidoarjo. The results showed that the involvement of students in coaching and mentoring NIB can have a positive impact by increasing the awareness and ability of MSME owners in taking care of their business licenses.